Beneficial bacteria as biocontrol agents for American foulbrood disease in honey bees (Apis mellifera). Issue 2 (22nd March 2023) - Ye, Manhong; Li, Xiaoyuan; Yang, Fengping; Zhou, Bin
Abstract: American foulbrood (AFB) is a cosmopolitan bacterial disease that affects honey bee ( Apis mellifera ) larvae and causes great economic losses in apiculture. Currently, no satisfactory methods are available for AFB treatment mainly due to the difficulties to eradicate the tenacious spores produced by the etiological agent of AFB, Paenibacillus larvae (Bacillales, Paenibacillaceae). This present review focused on the beneficial bacteria that displayed antagonistic activities against P. larvae and demonstrated potential in AFB control. Emphases were placed on commensal bacteria (genus Bacillus and lactic acid bacteria in particular) in the alimentary tract of honey bees. The probiotic roles lactic acid bacteria play in combating the pathogenic P. larvae and the limitations referring to the application of these beneficial bacteria were addressed.